2017
DOI: 10.1051/matecconf/201710301015
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Pervious Concrete Containing Scrap Tyre Tubes

Abstract: Abstract. There is a huge quantity of waste tyre tubes generated every year due to the increasing of motorcycle user. Therefore, recycling of the waste tyre tubes is become mandatory. The aim of this research was to study the properties of pervious concrete containing scrap tyre tube (STT) rubber particles with percentages of 3%, 5% and 7% of the cement content. The properties studied are void content, compressive strength measured at 7, 14 and 28 days, flexural strength and flow rate which were determined at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In this research the methodology applied for the preparation of pervious concrete specimens was from ASTM C192, with the moulds made of PVC pipe, in the dimensions of 200.0 mm (height) by 100.0 mm (diameter), and the characterization of the aggregates was done by granulometry test, ASTM C136, of pebble and limestone aggregates, approximately 4.5 mm to 9.0 mm in size, through sieving. The methodology applied to the rubber tyre reuse STT specimens was the one performed by Boon et al (2017). The pebble aggregate, Figure 1, originated from the Juruá River (Amazon), the limestone, Figure 2, originated from the crushing processing of rocks found in the neighboring cities of Manaus (Amazonia) and the STT, Figure 3, used in this research originated from discarded used tyres in the city of Manaus (Amazonia).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this research the methodology applied for the preparation of pervious concrete specimens was from ASTM C192, with the moulds made of PVC pipe, in the dimensions of 200.0 mm (height) by 100.0 mm (diameter), and the characterization of the aggregates was done by granulometry test, ASTM C136, of pebble and limestone aggregates, approximately 4.5 mm to 9.0 mm in size, through sieving. The methodology applied to the rubber tyre reuse STT specimens was the one performed by Boon et al (2017). The pebble aggregate, Figure 1, originated from the Juruá River (Amazon), the limestone, Figure 2, originated from the crushing processing of rocks found in the neighboring cities of Manaus (Amazonia) and the STT, Figure 3, used in this research originated from discarded used tyres in the city of Manaus (Amazonia).…”
Section: Methodsmentioning
confidence: 99%
“…The pebble aggregate, Figure 1, originated from the Juruá River (Amazon), the limestone, Figure 2, originated from the crushing processing of rocks found in the neighboring cities of Manaus (Amazonia) and the STT, Figure 3, used in this research originated from discarded used tyres in the city of Manaus (Amazonia). Recycling of used tires follows the methodology proposed by Boon et al (2017), carried out by processing the STT which is washed to remove impurities and cut into small rectangular shaped rubber particles, with an average size of 10.0 mm by 6.00 mm, for mixing during the manufacture of permeable concrete. The proportion of tube-rubber particles is 5% of the cement mass, about 19.0 kg/m³ of STT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 mix designs were used, and the results showed that it is possible to replace the aggregate with a crumb rubber but in correct proportion and with an appropriate granular size. Boon et al [9] also studied the properties of high permeable concrete but with the replacement of scrap tyre tubes. Their experimental studies have indicated that the use of scrap tyre tubes has increased the flow rate and void content.…”
Section: Introductionmentioning
confidence: 99%